Services and the U.S.-Canada relationship beyond the FTA - Whalley, John (Centre for International Studies [S.l.], 1992)
Looks at services in Canadian and United States economies. Examines the treatment of services in the Free Trade Agreement. Highlights US-Canada service issues in the 1990s.